Plausibility Under Duress: Counter-Narrative, Suspicion and Folk Forensic Contra-Plotting - Sorokin, Siim (Narrative Works, 2024)
How would it portend to analytical contextualization as well as specific theorization when instances where narrative kernels, once weaved into alternative epistemologies, make their way into, and become (re-)”plotted” on an inherently political platform, a session of state Parliament? Motivated by such an inquiry, the present multidisciplinary paper develops its theoretical argument by interrogating the notions of “counter-narrating” and “counter-narrative” cast on the intertwined conceptual landscape of forensics, tracking, and suspicion. The theoretical discussion is advanced further by developing the notions of productive suspicion and contra-plotting. On analytical level, the present chapter maintains that the narrative structure of some parliamentary discourses (presentations, Q&As) may operate much in the same manner as an anonymous forum thread or a reply chain in news’ commentaries. In undertaking this multidisciplinary theoretical discussion and analysis, the aim of this paper is to inform and expand the scholarship on counter-narratives and, in particular, to further solidify the conceptual aspects of the act, or practice, of counter-narrating.